Studi Keanekaragaman Bivalvia pada Zona Intertidal Pantai Sialang Buah Kabupaten Serdang Bedagai Provinsi Sumatera Utara - Miftahul Zannah; Ipanna Enggar Susetya (AQUACOASTMARINE, 2018)
This study aims to determine the bivalve community structure in the intertidal zone at Sialang Buah Beach and find out the relationship of physical, chemical, substrate factors with bivalve species diversity in Sialang Buah Beach. This research has been done in intertidal zone Sialang Buah beach at March until April 2018. The location of sampling was determined by Purposive Sampling method at 3 stasions. The sampling of bivalvia got from 6 plot of each stasion in intertidal zone. The result from the research was 6 bivalvia species. There are Meretrix meretrix, Meretrix lusoria, Anadara antiquata, Anadara gubernaculum,Glauconome rugosa and Perna viridis. The conciseness was between 21-60 ind/m2, The various was between 1,15-1,35 including medium catagory, the similarity was between 0,71-0,75 the domination was between 0,24-0,44. The correlation of Principal Component Analysis between the various of bivalvie to Nitrat, Fosfat, Do, pH and C-organic was positively. The visibility, temparature, salinity, depth and the current was negative.Keywords : Sialang Buah Beach, Intertidal Zone, Bivalvia, Community Structure, Water Quality